Regeneration Process of The Prosperous Justice Party (PKS) to Maintain Its Existence by Election Year 2014: Regeneration Process of The Prosperous Justice Party (PKS) to Maintain Its Existence by Election Year 2014 - Yusa Djuyandi; Fifi Lutfiah Sodikin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
Political parties prepare prospective national leaders through a political recruitment process. The Prosperous Justice Party (PKS), one of the Islamic parties In Indonesia, has a Regional Leadership Council (DPD) in each district or city. Regional Leadership Council (DPD) of Bandung City is interesting to study since it has a unique regeneration process and the organizations (under brow) have scored excellent cadres. This study aims to analyze the regeneration process of DPD PKS at Bandung City to maintain its existence in the 2014 election using the theory of political recruitment through the regeneration pathway proposed by Almond and Powell. The research was a qualitative method with data collection techniques carried out through secondary data collected by the General Elections Commission (KPU) of Bandung City. The primary data collected from PKS cadre interview process. This study found that the DPD PKS regeneration process of Bandung City affected the quality of promoted cadre, thus influencing the quality and existence of the party. The process of regeneration has produced excellent cadres through education and training stages that make it exist.